Testing the Public Officials’ Integrity in the Moonlighting of State-Owned Company Commissioner - Shalahuddin Haikal (Association of Certified Fraud Examiners Indonesia Chapter, 2023)
Conflict of interest is related to fraud and corruption, whose sources include the following, (a) concurrent positions or moonlighting, (b) public sector non-cooling off work/business activities post-employment, (c) work and personal business interests of family, friends, and associates, (d) affiliate relationship of community groups, organizations, and political aspirations. Therefore, this study aimed (1) to develop a catalogue of laws and regulations implicitly and explicitly prohibiting state officials or government employees from implementing moonlighting. It indicated the explicit prohibition of moonlighting against interfering with the conditions causing conflicts of interest. It also aimed (2) to examine the moonlighting of SOE commissioners through state officials. In this analysis, SOE was selected as the sample due to being simultaneously regulated by various policies prohibiting conflicts of interest and moonlighting. The sample was also exchange-listed because of the obligation to disclose information in the Capital Market Law as an Annual Report, where the profiles of the Commissioner members were often showcased. The results showed that moonlighting was unacceptable by public officials as commissioner members, regarding the compiled catalogue.